Adaptasi Instrumen Depression Literacy (D-Lit) Questionnaire Versi Bahasa Indonesia dengan Menggunakan Metode Rasch Model - Rizkiani Amalia; Yundianto, Devie (Journal of Research and Measurement in Psychology: JPPP, 2025)
Limited knowledge and misconceptions about psychological disorders, especially depression, often lead to negative attitudes towards sufferers. Efforts are needed to address this issue to reduce unwanted impacts. This study aims to determine how people's knowledge of depression and to adapt and analyze the psychometric properties of the Depression Literacy (D-Lit) Questionnaire instrument. This study analyzed the adapted Depression Literacy (D-Lit) Questionnaire instrument, with 225 participants aged 18-40 years, which later became 195 participants due to elimination. The analysis method used was the Rasch Model. This study looks at the reliability of person and item and rating scale based on Andrich Threshold. The results of the analysis obtained were the item reliability value reached 0.99 and the person reliability value with a value of 0.64. Alpha Cronbach's reliability was found to be 0.68 which indicates that there is sufficient interaction between item and person. There were 30 persons that did not meet the invariance test criteria so they were eliminated, and 4 items were eliminated because they did not meet the requirements of Outfit MNSQ and ZTSD and Pt Mean Corr. The raw variance contained in the analysis is 44.3% where this value has met the unidimensionality requirement. The analysis conducted almost all met the requirements of the Rasch Model.